Lactobacillus sp as a Probiotic for the Prevention of Clostridium difficile Associated Diarrhea - Ulfa Nur Rohmah; Saskiyanti Ari Andini; Hendrik Prayitno Luawo; Waluyo Waluyo; Yulia Indah Permata Sari (Universitas Airlangga, 2019)
Background: Antibiotic treatment can disturb the resistance of the gastrointestinal flora to colonization. This may result in complications, the most serious of which is Clostridium difficile associated diarrhea (CDAD). The aim of this study was to determine the effectiveness of probiotics for the prevention of CDAD.Method: The databases used were Scopus, Proquest, CINAHL, Medline, Pubmed and ScienceDirect, limited to having been published in the last 5 years. A literature review followed the keyword search. The keywords used were probiotics, Clostridium difficile, associated, diarrhea, randomized, control and trial using